Ante-Nicene Christian library: translations of the writings of the Fathers down to A. D. 325 - Roberts, Alexander; Donaldson, James (T. and T. Clark, 1867)
v.1. The Apostolic Fathers.--v.2. Justin Martyr and Athenagoras.--v.3. Tatian, Theophilus and the Clementine recognitions.--v.5. Ireneus, vol. 1.--v.6. Hippolytus, Bishop of Rome, vol. 1.--v.7. Tertullianus against Marcion.--v.9. Irenaeus, vol. 2. Hippolytus, vol. 2. Fragments of third century.--v.10. The writings of Origen.--v.11. The writings of Tertullian, vol. 1.--v.14. The writings of Methodius, etc.--v.15. The writings of Tertullian, vol. 2.--v.16. Apocryphal gospels, Acts and Revelations.--v.18. The writings of Tertullian, vol. 3.--v.19. The seven books of Arnobius Adversus Gentes.--v. 20. The writings of Gregory Thaumaturgus, Dionysius of Alexandria and Archelaus.--v.22. The works of Lactantius, vol. 2.--v.23. Origen contra Celsum, books 2-8.--v.24. Early liturgies and other documents.